A green acid leaching method for resource utilization of lithium-aluminum electrolyte
In the resource utilization process of lithium-containing aluminum electrolytes, high-temperature-cooling-low-temperature acid leaching and stirring process is adopted, medium-concentration acid decomposes aluminum electrolytes to form low-molecular specific electrolytes and sodium fluoride and other products, and hydrogen fluoride is recovered in situ , solve the problems of secondary pollution of hydrogen fluoride and high process costs in the prior art, and achieve low-cost and green resource utilization and good economic benefits.
Patent Information
- Application Number
- CN202311511874.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-11-14
AI Technical Summary
In the prior art, in the process of resource utilization of lithium-containing aluminum electrolytes, it is difficult to effectively avoid hydrogen fluoride gas generated during the acid leaching process, resulting in secondary pollution, and high process cost and limited economic benefits.
A green acid leaching method is adopted to decompose aluminum electrolyte through a high-temperature-cooling-low-temperature acid leaching stirring process, using medium concentration of acid to form low-molecular specific electrolytes, sodium fluoride and other products, and in situ through cooling and low-temperature processes Recycle hydrogen fluoride.
The low-cost and green resource utilization of lithium-containing aluminum electrolytes has been achieved, which avoids secondary pollution of hydrogen fluoride, reduces process costs, and improves economic benefits.
Smart Images

Figure CN117430144B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste treatment and recycling of aluminum electrolytic cells, and specifically discloses a green acid leaching method for resource utilization of lithium-aluminum electrolyte. Background Art
[0002] The importance of lithium as a strategic mineral is becoming increasingly prominent, and lithium is called "an important element that drives the world forward."
[0003] Sodium oxide reacts with aluminum fluoride in cryolite, consuming aluminum fluoride in the electrolyte to produce sodium fluoride, resulting in a high electrolyte molecular ratio. Aluminum fluoride needs to be continuously added to the electrolytic cell to maintain a stable electrolyte molecular ratio. However, if the lithium salt content in the electrolyte is too high, the electrolyte primary crystallization temperature will decrease and the electrolyte superheat will increase, affecting the normal operation of the electrolytic cell and reducing the current efficiency. Therefore, lithium-rich electrolytes are often abandoned or stored. If they are not effectively recovered, it will cause a serious waste of lithium resources.
[0004] At present, a variety of processes have been proposed for the resource utilization of lithium-aluminum electrolytes, such as direct acid leaching, concentrated acid roasting leaching, alkali roasting leaching, acidic aluminum salt leaching, etc. The direct acid leaching method uses inorganic acids (such as CN109055763A, CN107915238A, CN107974565A, etc.) and organic acids (such as CN115947356A, etc.) to leach aluminum electrolytes. It has low cost, simple process, and is easy to achieve large-scale production. However, the hydrogen fluoride gas generated in the process is difficult to control and is prone to secondary pollution; the concentrated acid roasting leaching method uses concentrated sulfuric acid to react with aluminum electrolytes to prepare hydrogen fluoride and recover lithium resources (such as CN113772630A, CN112777621A, etc.), but this process has high equipment requirements, high cost, and concentrated acid is also prone to environmental pollution; alkali roasting leaching The method converts water-insoluble / acid-soluble lithium salts into water-soluble / acid-soluble lithium salts by adjusting the physical phase of lithium in the electrolyte, and selective lithium recovery can be achieved through water / acid washing (such as CN105543504A, CN110240182A, etc.), but the high-temperature treatment process before leaching is costly and has limited economic benefits; the acidic aluminum salt leaching method uses aluminum salts to leach aluminum electrolytes under acidic conditions to form aluminum complexes, and can improve the selectivity of lithium leaching in aluminum electrolytes (such as CN114438239A, CN105348786A, etc.), but similar to the direct leaching method, hydrogen fluoride gas is still inevitably produced during the leaching process.
[0005] Therefore, how to avoid secondary pollution caused by hydrogen fluoride produced during the acid leaching process of aluminum electrolyte and realize low-cost and green resource utilization of lithium-aluminum electrolyte is a technical problem that needs to be solved urgently in the industry. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a green acid leaching method for resource utilization of lithium-aluminum electrolyte. The method has a simple treatment process and can recover sodium fluoride and lithium carbonate products, thereby realizing low-cost harmless treatment of waste electrolytes from aluminum electrolysis cells.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A green acid leaching method for resource utilization of lithium-aluminum electrolyte, comprising the following steps:
[0009] S1. crushing, grinding and sieving the electrolyte block to obtain an electrolyte powder having a particle size of less than 250 μm;
[0010] S2. Add the electrolyte powder and sodium salt obtained in step S1 to the acid solution, stir and filter to obtain a filter residue 1 and a filtrate 1; the acid solution is one of hydrochloric acid, sulfuric acid and nitric acid; the sodium salt is one of sodium chloride, sodium sulfate and sodium nitrate, and the type of the sodium salt is consistent with the type of acid radical ions of the acid solution;
[0011] S3. The filter residue 1 obtained in step S2 is added to water, stirred and filtered to obtain a filter residue 2 and a filtrate 2, the filter residue 2 is washed and dried to obtain a low molecular weight electrolyte product, and the filtrate 2 is evaporated, crystallized and dried to obtain a sodium fluoride product;
[0012] S4. Sodium hydroxide is added to the filtrate 1 obtained in step S2 to adjust the pH of the solution, and after stirring and filtering, a filter residue 3 and a filtrate 3 are obtained, and the filter residue 3 is dried to obtain an aluminum hydroxide product; the pH of the solution is adjusted in the range of 5-10;
[0013] S5. The filtrate 3 obtained in step S4 is concentrated and filtered to obtain a filter residue 4 and a filtrate 4, and the filter residue 4 is dried to obtain a sodium salt product;
[0014] S6. Add sodium carbonate to the filtrate 4 obtained in step S5, and obtain a lithium carbonate product after stirring, filtering, washing and drying.
[0015] Furthermore, in step S2, the liquid-to-solid ratio of the electrolyte powder to the acid solution is 5-30 g / L, the acid concentration is 0.5-2 mol / L, and the amount of sodium salt added is 0-20% of the mass of the electrolyte powder.
[0016] Furthermore, the stirring process in step S2 is carried out in a closed reactor.
[0017] Furthermore, the stirring process of step S2 is a process of first high temperature, then cooling, and finally low temperature.
[0018] Furthermore, the high temperature is 50-95°C, the duration is 0.5-6h, the cooling rate is 0.5-5°C / min, the low temperature is 10-30°C, and stirring is performed for 0.5-6h after reaching the low temperature.
[0019] Beneficial effects of the present invention: The present invention proposes a green acid leaching method for resource utilization of lithium-aluminum electrolytes, which uses medium-concentration acid to achieve resource disposal of lithium-containing electrolytes and recover lithium in the form of lithium carbonate. Compared with the prior art, the present invention recovers hydrogen fluoride generated during the acid leaching of lithium-containing electrolytes in situ, does not generate secondary pollution, and is green and environmentally friendly; and the technical solution of the present invention does not involve a high-temperature roasting process, and the cost of using common inorganic acids for disposal is low and easy to industrialize; furthermore, the present invention has a variety of products, and low-molecular-weight electrolyte products can be directly returned to the electrolytic cell to form an electrolyte regulator for use, and products such as sodium fluoride and lithium carbonate have high value and good economic benefits.
[0020] Technical principle of the present invention: The present invention realizes the decomposition of aluminum electrolyte by medium-concentration acid through the high-temperature-cooling-low-temperature acid leaching stirring process to form low-molecular-weight electrolyte and sodium fluoride. The acid is consumed first and then generated in the whole process, and is not consumed in the whole process, acting as a "catalyst". After hydrogen fluoride is generated, it is recovered in situ through cooling and low-temperature processes. Specifically, in the high-temperature stirring acid leaching process, medium-concentration acid reacts with aluminum electrolyte to generate low-molecular-weight substances, hydrogen fluoride, sodium salt and aluminum salt. Through cooling and low-temperature processes, sodium salt can react again with hydrogen fluoride dissolved in the solution to generate sodium fluoride that is difficult to react with medium-concentration acid at low temperature; the addition of sodium salt in the acid leaching process can promote the decomposition of aluminum electrolyte and the formation of sodium fluoride, and at the same time, due to the common ion effect of sodium, the dissolution of sodium fluoride in water is inhibited; the acid leaching process is carried out in a closed reactor, which can effectively alleviate the volatilization of hydrogen fluoride in the high-temperature leaching process, so that it can be fully recovered by cooling and low-temperature processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0022] Figure 1 This is a process flow chart of a green acid leaching method for resource utilization of lithium-containing aluminum electrolytes of the present invention. The raw material is a lithium-containing electrolyte block, and after acid leaching treatment, low molecular weight electrolyte, sodium fluoride, lithium carbonate, aluminum hydroxide and sodium chloride products are obtained, realizing the green resource utilization of aluminum electrolytes.
[0023] Figure 2 This is the SEM-EDS image of the filter residue 1 in Example 1.
[0024] Figure 3 This is the XRD diagram of the lithium carbonate product in Example 1. DETAILED DESCRIPTION
[0025] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] S1. crushing, grinding and sieving the electrolyte block to obtain an electrolyte powder having a particle size of less than 250 μm;
[0028] S2. In a closed reactor, add electrolyte powder and sodium chloride to hydrochloric acid, stir and filter to obtain residue 1 and filtrate 1, with a liquid-to-solid ratio of 15 g / L, an acid concentration of 1 mol / L, and an amount of sodium salt added of 5% of the mass of the electrolyte powder. The initial stirring temperature is 65°C, the duration is 2 hours, then the temperature is lowered to 10°C at a rate of 0.5°C / min, and then stirred for another 6 hours. The residue 1 was tested and analyzed by SEM-EDS. The electrolyte powder was decomposed by hydrochloric acid to form a low molecular weight electrolyte and sodium fluoride. The results are attached. Figure 2 ;
[0029] S3. The residue 1 is added to water, stirred and filtered to obtain a residue 2 and a filtrate 2, the residue 2 is washed and dried to obtain a low molecular weight electrolyte product, and the filtrate 2 is evaporated, crystallized and dried to obtain a sodium fluoride product;
[0030] S4. Sodium hydroxide was added to the filtrate 1 to adjust the pH of the solution to 5, and after stirring and filtering, a filter residue 3 and a filtrate 3 were obtained, and the filter residue 3 was dried to obtain an aluminum hydroxide product;
[0031] S5. The filtrate 3 is concentrated and filtered to obtain a residue 4 and a filtrate 4, and the residue 4 is dried to obtain a sodium chloride product;
[0032] S6. Sodium carbonate is added to the filtrate 4 obtained in step S5, and a lithium carbonate product is obtained after stirring, filtering, washing and drying. The physical phase of the lithium carbonate product is analyzed by XRD test, and relatively pure lithium carbonate is obtained in this embodiment.
[0033] According to ICP test analysis, the dissolution rate of electrolyte powder under the action of hydrochloric acid is 35%, the sodium dissolution rate is 45%, the lithium dissolution rate is 40%, and 90% of the dissolved sodium is recovered in the form of sodium fluoride.
[0034] Embodiment 2:
[0035] S1. crushing, grinding and sieving the electrolyte block to obtain an electrolyte powder having a particle size of less than 250 μm;
[0036] S2. In a closed reactor, add electrolyte powder and sodium chloride to hydrochloric acid, stir and filter to obtain residue 1 and filtrate 1, with a liquid-to-solid ratio of 30 g / L, an acid concentration of 0.5 mol / L, and an amount of sodium salt added of 5% of the mass of the electrolyte powder. Stirring was initially carried out at 50°C for 6 hours, then cooled to 15°C at a rate of 1°C / min, and then stirred for another 3 hours;
[0037] S3. The residue 1 is added to water, stirred and filtered to obtain a residue 2 and a filtrate 2, the residue 2 is washed and dried to obtain a low molecular weight electrolyte product, and the filtrate 2 is evaporated, crystallized and dried to obtain a sodium fluoride product;
[0038] S4. Sodium hydroxide was added to the filtrate 1 to adjust the pH of the solution to 6, and after stirring and filtering, a filter residue 3 and a filtrate 3 were obtained, and the filter residue 3 was dried to obtain an aluminum hydroxide product;
[0039] S5. The filtrate 3 is concentrated and filtered to obtain a residue 4 and a filtrate 4, and the residue 4 is dried to obtain a sodium chloride product;
[0040] S6. Add sodium carbonate to the filtrate 4 obtained in step S5, and obtain a lithium carbonate product after stirring, filtering, washing and drying.
[0041] After testing and analysis, the dissolution rate of the electrolyte powder under the action of hydrochloric acid was 15%, the sodium dissolution rate was 20%, the lithium dissolution rate was 17%, and 92% of the dissolved sodium was recovered in the form of sodium fluoride.
[0042] Embodiment 3:
[0043] The steps are the same as those in Example 2, except that in step S2, the liquid-to-solid ratio is 5 g / L, the acid concentration is 2 mol / L, and the amount of sodium salt added is 20% of the mass of the electrolyte powder. The initial stirring temperature is 95°C, the duration is 4 hours, and then the temperature is lowered to 20°C at a rate of 1°C / min, and then stirred for another 4 hours.
[0044] After testing and analysis, the dissolution rate of the electrolyte powder under the action of hydrochloric acid was 58%, the sodium dissolution rate was 65%, the lithium dissolution rate was 60%, and 96% of the dissolved sodium was recovered in the form of sodium fluoride.
[0045] Embodiment 4:
[0046] The steps are the same as those in Example 2, except that in step S2, the liquid-to-solid ratio is 20 g / L, the acid concentration is 1 mol / L, and the amount of sodium salt added is 0% of the mass of the electrolyte powder. The initial stirring temperature is 80°C, the duration is 0.5 h, and then the temperature is lowered to 20°C at a rate of 5°C / min, and then stirred for another 0.5 h.
[0047] After testing and analysis, the dissolution rate of the electrolyte powder under the action of hydrochloric acid was 36%, the sodium dissolution rate was 45%, the lithium dissolution rate was 38%, and 79% of the dissolved sodium was recovered in the form of sodium fluoride.
Claims
1. A green acid leaching method for resource utilization of lithium-aluminum electrolyte, characterized in that: The steps include: S1. crushing, grinding and sieving the electrolyte block to obtain an electrolyte powder having a particle size of less than 250 μm; S2. Add the electrolyte powder and sodium salt obtained in step S1 to the acid solution, stir and filter to obtain a filter residue 1 and a filtrate 1; the acid solution is one of hydrochloric acid, sulfuric acid and nitric acid; the sodium salt is one of sodium chloride, sodium sulfate and sodium nitrate, and the type of the sodium salt is consistent with the type of acid radical ions of the acid solution; The stirring process is carried out in a closed reactor; the stirring process is a process of first high temperature, then cooling, and finally low temperature; S3. The filter residue 1 obtained in step S2 is added to water, stirred and filtered to obtain a filter residue 2 and a filtrate 2, the filter residue 2 is washed and dried to obtain a low molecular weight electrolyte product, and the filtrate 2 is evaporated, crystallized and dried to obtain a sodium fluoride product; S4. Sodium hydroxide is added to the filtrate 1 obtained in step S2 to adjust the pH of the solution, and after stirring and filtering, a filter residue 3 and a filtrate 3 are obtained, and the filter residue 3 is dried to obtain an aluminum hydroxide product; the pH of the solution is adjusted in the range of 5-10; S5. The filtrate 3 obtained in step S4 is concentrated and filtered to obtain a filter residue 4 and a filtrate 4, and the filter residue 4 is dried to obtain a sodium salt product; S6. Add sodium carbonate to the filtrate 4 obtained in step S5, and obtain a lithium carbonate product after stirring, filtering, washing and drying.
2. A green acid leaching method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: In step S2, the liquid-to-solid ratio of the electrolyte powder to the acid solution is 5-30 g / L, the acid concentration is 0.5-2 mol / L, and the amount of sodium salt added is 0-20% of the mass of the electrolyte powder.
3. A green acid leaching method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The high temperature is 50-95°C, the duration is 0.5-6h, the cooling rate is 0.5-5°C / min, the low temperature is 10-30°C, and stirring is performed for 0.5-6h after reaching the low temperature.
Citation Information
Patent Citations
Plasma modified nylon membrane process method
CN105348786A
Method for extracting lithium salt from aluminum electrolyte by utilizing fluoride roasting and acid leaching
CN105543504A
Method for selective sulfuric acid leaching of lithium in aluminum electrolyte
CN107915238A
Method for selectively leaching nitric acid from lithium element in aluminum electrolyte
CN107974565A
Method for selective hydrochloric acid leaching of lithium element from aluminum electrolyte
CN109055763A